Accounting for retarded weathering products in comparing methods for quantifying carbon dioxide removal in a short-term enhanced weathering study - te Pas, Emily E. E. M.; Chang, Elliot; Marklein, Alison R.; Comans, Rob N. J.; Hagens, Mathilde (Frontiers in Climate, 2025)
Various approaches are currently used to quantify the carbon dioxide removal (CDR) associated with enhanced weathering (EW), which involves amending soils with crushed silicate minerals. We aimed to contribute to the development of a standardized procedure for CDR quantification by complementing the results of a recently published soil column experiment, in which crushed olivine, wollastonite, and albite were added to soils, with total fusion ICP-OES analyses of base cation concentrations. CDR quantified by soil-based mass balance approaches was only comparable to leachate-based total alkalinity measurements after correcting for the weathering products that were retained within the soil profile, which we defined as the retarded fraction. The retarded fraction comprised 92.7–98.3% of the weathered cations, indicating that at least in our short-term study (64 days), the majority of weathering products were retained within the soil. Further investigation of the fate of retarded weathering products showed that small portions precipitated as carbonate minerals (up to 34.0%) or adsorbed to reactive surfaces, such as soil organic matter and clay minerals (up to 32.5%). Hence, a large portion of weathering products may be retained in the soil due to strong adsorption and/or further mineral precipitation reactions (31.6–92.7%), with potentially important implications for the quantification of CDR across time. We conclude that soil-based mass balance approaches are useful in quantifying weathering rates and can infer potential CDR; however, the actual CDR realized for a given time and depth interval can only be constrained after accounting for the retarded fraction.